Haemosporidian lineages FASTA - Drovetski, Sergei V.; Aghayan, Sargis A.; Mata, Vanessa A.; Lopes, Ricardo J.; Mode, Nicolle A.; Harvey, Johanna A.; Voelker, Gary (Dryad Digital Repository, 2014)
The data file is a FASTA alignment of unique haemosporidian lineages identified in the bird samples. The name of each lineage corresponds to the parasite lineage identifier used in the manuscript and associated files. Lineages are identified to genus when species identification was not possible.